Exploring EFL Students’ Perspectives: The Role of TikTok in Enhancing English Language Skills - Susanto, Alifarga Kresnayoga; Suparmi, Suparmi (Journal of English for Academic and Specific Purposes (JEASP), 2024)
Presently, numerous media platforms are available for autonomous English learning, with TikTok emerging as a popular option. This study explores students' perspectives on employing TikTok as a tool for English learning. Twenty participants from the 2022 English Language Education program who utilized TikTok for English learning completed questionnaires, with five students participating in interviews. The selection of participants was carried out through purposive sampling. Employing a descriptive qualitative approach, data collection involved questionnaires and interviews. Thematic analysis revealed that students utilized TikTok for multiple language skills and its component such as listening, speaking, reading, writing, grammar, vocabulary, and pronunciation. TikTok aided vocabulary expansion and contextual understanding of grammar. Although challenges like accuracy and content quality variations existed, most students recommended TikTok to enrich English learning experiences.